Perbandingan Nilai CRP Metode Sandwich Immunometri Dan Metode Fia Pada Sampel Darah Vena Pasien Terindikasi Infeksi Di Rumah Sakit - Juraijin, Denny; Rahmayani, Sari (Indobiosains, 2025)
Checking blood levels of C-Reactive Protein (CRP) is one of the tests that can detect inflammation at an early stage. C-Reactive Protein (CRP) is an inflammatory marker that is synthesized in the liver. CRP levels increase due to trauma, bacterial infection and inflammation (inflammation and tissue damage). CRP plays an important role in the recognition of microbial organisms and as an immunomodulator in the body's defense system, CRP also plays a role in the recognition of necrotic tissue. Specimens that can be used for C-Reactive Protein examination are Serum, heparin plasma, and EDTA plasma C-Reactive Protein (CRP) examination consists of several methods, including the Latex method, automatic and others. The research design used posttest only design. This study was conducted in April 2023 at the Laboratory of RSU Bunda Palembang which amounted to 21 samples using venous blood samples Results: the results of CRP examination using the FIA method were 9.53 mg/L and CRP examination using the Sandwich Immunometry method was 9.43 mg/L. The results of the research data were analyzed using spss with the Dependent T test. There is no difference in CRP values between the Sandwich Immunometry method and the FIA method in venous blood samples of patients with indications of infection at Bunda Hospital Palembang in 2023.